Diffusion coefficients of lead (II) nitrate in nitric acid aqueous solutions at 298 K - Valente, Artur J. M. (2004)
Interdiffusion coefficients of lead (II) nitrate in water and in nitric acid (10-5-10-2 M) mixtures at 298.15 K, and at concentrations from 0.001 to 0.1 M, have been measured using a conductimetric cell and an automatic apparatus to follow diffusion. The cell uses an open-ended capillary method and a conductimetric technique is used to follow the diffusion process by measuring the resistance of a solution inside the capillaries, at recorded times. The diffusion of lead (II) nitrate is clearly affected by the presence of HNO3 as well as by the lead (II) hydrolysis. At the highest HNO3 concentration (0.01 M) the effect of the hydrogen ions on the whole diffusion process has an important and main role, whilst at the highest Pb(II) concentration the presence of HNO3 as well as the hydrolysis can be neglected. These values are supported by UV-spectroscopy as well as by pH measurements. The experimental interdiffusion coefficients are discussed on the basis of the Onsager-Fuoss model.